2020
DOI: 10.29121/granthaalayah.v7.i11.2020.368
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Replacement of Cement Using Silica Fume and Fine Aggregate Using Glass Powder

Abstract: Increase in population results in increase in usage of materials which cause much pollution to environmental surroundings if not disposed properly. Replacement of costlier building material by disposable waste material is one of best engineering practice in construction. In this paper replacement of cement using silica fume is done up to 20% and replacement of fine aggregate using glass powder is done up to 40% also silica fume  and glass powder are replaced by 15% and 20%.compressive strength for replaced mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The reason for the increase in STS of silica fumecontaining concrete mixes was the same as for the increase in compressive strength [37]. Silica fume has been shown to boost the STS of concrete in previous experiments [12,[72][73][74][75][76][77].…”
Section: Split Tensile Strength (Sts)mentioning
confidence: 90%
“…The reason for the increase in STS of silica fumecontaining concrete mixes was the same as for the increase in compressive strength [37]. Silica fume has been shown to boost the STS of concrete in previous experiments [12,[72][73][74][75][76][77].…”
Section: Split Tensile Strength (Sts)mentioning
confidence: 90%
“…A study showed that, at 10% replacements, the compressive strength increased by about 31%, 16%, and 9% at 7, 14, and 28 days of curing for the reference concrete, respectively [ 77 ]. Similarly, a study reported that compressive strengths at 7- and 28-days curing are about 3 to 4% higher than conventional concrete at 15% replacement of waste glass with cement [ 78 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The research was carried out on partial cement replacement with the waste glass in concrete at 0%, 5%, 10%, and 15%. Results indicated that concrete split tensile strength was improved up to 10% replacement cement with waste glass [ 77 ]. A researcher concluded that the split tensile strength of concrete increased with up 10% substitution of waste glass and then decreased gradually, having maximum strength at 10% substitution of waste glass [ 60 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations